Microextraction by Packed Sorbent as a Clean-up Approach for the Determination of Ketamine and Norketamine in Hair by Gas Chromatography–Tandem Mass Spectrometry. Issue 3 (17th September 2022) - Simão, A Y; Oliveira, P; Rosendo, L M; Rosado, T; Andraus, M; Barroso, M; Gallardo, E
Abstract: The use of new psychoactive substances has been increasing and constitutes a social and public health problem, and hence, toxicological analysis has become of utmost importance for the detection of such substances. In this article, we present the development and full validation of a simple, user and environmentally friendly, cheap and suitable method for the determination of ketamine and its main metabolite norketamine in hair samples. The procedure included using a miniaturized procedure—microextraction by packed sorbent with mixed-mode sorbent—for sample clean-up. Organic solvents use was minimal, and it was possible to obtain a linear method (0.05–10 ng/mg for both analytes). The extraction efficiency ranged from 32 to 61%, which did not impair sensitivity. The method proved to be selective, precise, accurate and suitable for routine analysis for the determination of said compounds in 50-mg hair samples.